Urgensi Akta Ikrar Wakaf sebagai Alternatif Penyelesaian Sengketa Tanah - Bukido, Rosdalina; Misbahul Munir Makka (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This paper was to identify the truth and position of waqf that occurred in Bongkudai Village, East Bolaang Mongondow District, Indonesia and to determine ways to resolve the problems that happened in the village. There are problems regarding waqf land which is used for personal interests and the issue of land payment receipts intended for waqf makes the writer have the intention to prepare this study. The method used by the author in the completion of this study was a qualitative method whose approach is a descriptive approach, by prioritizing interviews and field facts as the main source, for data collection conducted by the author was observation, interviews, and documentation to get concrete data and facts that occur in the field. The results obtained are that land which is known as waqf land has been partly used for personal use. Besides, there is a problem with the receipt in question. The land that is known as waqf land should never be used for individual interests. A receipt is actually not an urgent matter in a problem, as long as the disputing party has no evidence to oppose it. Therefore it must be a land payment receipt intended for waqf to directly record the endowment so that problems do not occur in the future.